Reconstruction of the Concept of Interfaith Dialogue from the Perspective of Religious Moderation - Afriani Afriani; Anggun Tammas Maharani; Sukma Aulia Hanifa (Jurnal Indonesia Studi Moderasi Beragama, 2026)
Background: This article is grounded in the reality that interfaith dialogue practices in plural societies tend to be formalistic, elitist, and confined to theological discourse, and therefore have not fully addressed the challenges of intolerance, social polarisation, and disinformation. Objective: This study aims to reconstruct the concept of interfaith dialogue from the perspective of religious moderation to make it more inclusive, contextual, and applicable. Method: The research employs a qualitative method with a constructive-critical approach, grounded in a literature review, and is analysed through stages of deconstruction, critical-comparative analysis, and conceptual reconstruction. Result: The findings indicate the need for a shift in the orientation of dialogue from symbolic-theological to social-transformative, integrating the values of tawazun (balance), tasamuh (tolerance), i‘tidal (justice), and national commitment. The proposed dialogue model is inclusive and participatory, relational and empathetic, and adaptive to contemporary challenges, including those in the digital sphere. Conclusion: Reconstructing interfaith dialogue based on religious moderation can strengthen social cohesion and national harmony. Contribution: This study contributes by reinforcing a theoretical framework of dialogue as a relational paradigm and by offering a conceptual model that may serve as a reference for developing interreligious harmony programs and religious moderation policies.